Jair Bolsonaro's X-ray - Pacheco Dávila, Gabriela M. (2021)
This paper aims to present the most representative singularities and irregularities of former candidate Jair Bolsonaro in publicity videos broadcast during the 2018 presidential campaign focused on the use of body language. Through the qualitative methodology with procedure in the analysis of images and videos with inspiration in concepts of semiotics of culture. The analysis made it possible to understand that body language is relevant in the electoral period, since it is a time when candidates are more sympathetic, allowing spatial limits to be reduced, in addition to aggressive speeches and strange props that make up the semiosphere of the electoral campaign.